Preparation, Modeling, and Optimization of Mechanical Properties of Epoxy/H I PN/Silica Hybrid Nanocomposite Using Combination of Central Composite Design and Genetic Algorithm. Part 2. Studies on Flexural, Compression, and Impact Strength - Rostamiyan, Y.; Fereidoon, A.B.; Omrani, A.; Ganji, D.D. (Проблемы прочности, 2013)
In spite of good tensile strength of epoxy resins,
they have brittle nature and show poor resistance
to crack propagation. In view of enhancing
mechanical strength and fracture toughness
of epoxy-based nanocomposite simultaneously,
a new combination of thermoplastic and particulate
nanofiller is used as a modifier. Here, the obtained
ternary epoxy-based nanocomposite
includes high impact polystyrene (HIPS) as thermoplastic
and silica nanoparticles as its particulate
phases. Flexural, compression and impact
were the three different mechanical tests investigated,
in order to achieve higher strength without
attenuating other desired mechanical
properties. Central composite design (CCD) is
employed to present mathematical models to predict
mechanical behaviors of epoxy/HIPS/silica
nanocomposite as a function of physical factors.
The effective parameters investigated were
HIPS, SiO₂ and hardener contents. Based on
mathematical functions obtained from CCD
model, the genetic algorithm – as one of the
most powerful optimization tools – is applied to
find the optimum values of mentioned mechanical
properties. We have found that a combination
of HIPS and silica nanoparticles
significantly increase compressive and impact
strengths of epoxy resin up to 57 and 421%, respectively.
Although flexural strength did not
change positively, the elongation at break for
flexural one increased up to 144%. Finally, the
morphology of fracture surface was studied by
energy-dispersive X-ray spectroscopy and scanning
electron microscopy. Несмотря на то что эпоксидные смолы обладают высоким пределом прочности при растяжении, они хрупкие и характеризуются слабым сопротивлением развитию трещины. С целью
улучшения механической прочности и вязкости разрушения эпоксидных нанокомпозитов в
качестве модификатора использовали новый комбинированный термопластичный дисперсный нанонаполнитель. Полученный трехкомпонентный эпоксидный нанокомпозит содержит
ударопрочный полистирол в виде термопластичных и кремнеземных наночастиц, представляющих его дисперсные фазы. Чтобы получить более высокие показатели прочности без
воздействия на другие заданные механические показатели, проводили испытания на прочность при изгибе и сжатии и на ударную вязкость. Для представления математических
моделей с целью прогнозирования механического поведения гибридного нанокомпозита в
качестве функции физических факторов использовали центральный композиционный план.
Исследовали содержание ударопрочного полистирола, кремнезема и упрочняющего элемента
в нанокомпозите. На основе математических функций, полученных по модели центрального
композиционного плана, для выведения оптимальных значений механических свойств использовали генетический алгоритм, являющийся одним из самых мощных средств оптимизации.
Установлено, что сочетание наночастиц на основе ударопрочного полистирола и кремнезема
значительно увеличивает сопротивление эпоксидной смолы сжатию и удару на 57 и 421%
соответственно. При сопротивлении изгибу положительных изменений не наблюдается,
удлинение при изгибном разрыве увеличивается до 144%. С помощью энергодисперсионного
рентгеновского излучения и сканирующей электронной микроскопии проведено исследование
морфологии поверхности разрушения. Незважаючи на те що епоксидні смоли мають хорошу границю міцності при
розтязі, вони крихкі і характеризуються слабким опором розвитку тріщини. Із
метою покращання механічної міцності і в’язкості руйнування епоксидних
нанокомпозитів як модифікатор використовували новий комбінований термопластичний дисперсний наповнювач. До складу отриманого трикомпонентного епоксидного нанокомпозита входить удароміцний полістирол у вигляді
термопластичних і кремнеземних наночастинок, що являють собою його
дисперсні фази. Щоб отримати більш високі показники міцності без впливу
на інші задані механічні показники, проводили випробування на міцність при
згині і стиску та на ударну в’язкість. Для представлення математичних
моделей з метою прогнозування механічної поведінки гібридного нанокомпозита як функцію фізичних чинників використали центральний композиційний
план. Досліджували вміст удароміцного полістиролу, кремнезему і зміцнювального елемента в нанокомпозиті. На основі математичних функцій, отриманих за моделлю центрального композиційного плану, для виведення оптимальних значень механічних властивостей використовували генетичний алгоритм, що є одним із найміцніших засобів оптимізації. Установлено, що
поєднання наночастинок на основі удароміцного полістиролу і кремнезему
збільшує опір епоксидної смоли стиску на 57%, удару – на 421%. У той же
час позитивних змін при опорі згину не відмічається, видовження за згинального розриву збільшується до 144%. Проведено дослідження морфології
поверхні руйнування за допомогою енергодисперсійного випромінювання і
сканувальної електронної мікроскопії.